Characterisation of optimal dual measures via distortion - Monoyios, M (2006)
We derive representations for optimal martingale measures in a two-factor Markovian model, by seeking ramifications of a distortion power solution (Zariphopoulou (2001)) of the primal utility maximisation problem, for the dual problem. This provides an alternative to existing methods in the literature for characterising optimal measures, and gives new results in the form of a novel representation for the dual stochastic control problem, and in the form of Esscher transform relations between the optimal measure and the minimal measure. © Springer-Verlag 2006.